QuiC2 represents a functionally distinct class of dehydroshikimate dehydratases identified in Listeria species including Listeria monocytogenes. (30th March 2020) - Xue, Kevin; Prezioso, Stephanie M.; Christendat, Dinesh
Summary: Many Listeria species including L. monocytogenes contain the pathway for the biosynthesis of protocatechuate from shikimate and quinate. The qui1 and qui2 operons within these Listeria spp. encode enzymes for this pathway. The diversion of shikimate pathway intermediates in some Listeria species to produce protocatechuate suggests an important biological role for this compound to these organisms. A total of seven ORFs, including quiC2, were identified within qui1 and qui2, however only three proteins encoded by the operons have been functionally annotated. The final step in Listeria 's protocatechuate biosynthesis involves the conversion of dehydroshikimate by a dehydroshikimate dehydratase (DSD). In this study, we demonstrate that QuiC2 functions as a DSD in Listeria spp. through biochemical and structural analyses. Moreover, we show that QuiC2 forms a phylogenetic cluster distinct from other functionally annotated DSDs. The individual phylogenetic clusters of DSD are represented by enzymes that produce protocatechuate for distinct biological processes. Similarly, QuiC2 is expected to produce protocatechuate for a novel biological process. We postulate that protocatechuate produced by DSDs found within the QuiC2 phylogenetic cluster provides an ecological niche for representative organisms.